ASSOCIATION BETWEEN OBESITY INDUCED HYPERTENSION AND CONSUMPTION OF JUNK FOOD AMONG UNIVERSITY STUDENTS OF DISTRICT SIALKOT - NAEEM , W; ASHRAF, S; FATIMA, R; MALIK, A; KHARL , HAA; SHABBIR , A (Biological and Clinical Sciences Research Journal, 2023)
The principal cause of early death throughout the world is cardiovascular diseases (CVDs). It has been found that, in young adults, high blood pressure (BP) is considered a significant public health concern, with approximately 26.4% of global prevalence. A diet containing junk food is the preliminary cause of obesity, which leads to hypertension and other cardiovascular diseases in adults. The risk factors are prevailing at an alarming rate and have affected university students’ physical and mental health. Moreover, these health concerns have caused low productivity among students as well. This problem has not been studied and analyzed in sufficient profundity. This cross-sectional and correlational study investigated the relationship between fast food consumption, obesity, and hypertension among university students. This cross-sectional study was conducted on a sample size of three hundred participants aged twenty-five to forty. To calculate the BMI, the weight and height of the participants were measured, along with the measurements of their systolic and diastolic blood pressure and age, through standard tools and procedures. Their dietary intake was assessed using a questionnaire of food intake that records a 168-hour food intake. The study results revealed that significant positive correlations of high strength between fast food consumption and obesity were found using Spearman rank order correlations (rs = 0.81) and moderate strength of positive correlation between frequent fast-food consumption and hypertension (rs = 0.58). The resultant conclusion of the study shows that junk food is strongly linked with obesity and prehypertension. The findings of the study can reduce the prevalence of obesity and hypertension.